Flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material and preparation method thereof
By imitating the sponge structure in the coating, modifying and combining polymer resin with nano-inorganic particles with silicone, the problems of single coating performance and weak adhesion are solved, and the efficient preparation of multifunctional coatings is achieved, with excellent Flame retardant, anti-seepage, anti-fouling and fire resistance.
Patent Information
- Application Number
- CN202411385216.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The existing coatings have problems such as single performance, weak adhesion, poor durability and complex production process when protecting materials, and the heat resistance efficiency of flame retardant materials is poor, and the adhesion of inorganic nanoparticles in porous and capillary channel structures. Lower force.
By mimicking the porous and capillary channel structure characteristics inside and outside the sponge, flame retardant fillers of different shapes and particle sizes are dispersed in aqueous emulsions, the porous and capillary channel structures are constructed using silicone wrapping modifications, and combined with low surface energy Polymer resins and nano-inorganic particles enhance the density, flame retardancy and superhydrophobicity of the coating, and the preparation process is carried out at room temperature.
It realizes the versatility of the coating, has good anti-seepage, anti-fouling, corrosion resistance and flame retardant properties, has strong adhesion, simple preparation method, and is easy to be widely used in different substrates.
Abstract
Description
Technical Field
[0001] The invention relates to a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material and a preparation method thereof, belonging to the technical field of coating preparation. Background Art
[0002] Materials such as wood, plastic, and steel structures are increasingly used in electricity, electrical appliances, furniture manufacturing, and mechanical equipment, but they also face many problems, such as fire, high temperature, high humidity, salinity, and chemical corrosion. Using coatings for protection is a common and cost-effective method, but most coatings currently have problems such as single performance, weak adhesion, poor durability, and complex manufacturing processes. Based on this, the present invention discloses a flame-retardant, super-hydrophobic, anti-seepage, and anti-fouling multifunctional coating material and a preparation method thereof. This multifunctional coating imitates the interconnected structural characteristics of the porous and capillary channels existing inside and outside the sponge, disperses different flame-retardant fillers in the shape of linear, flaky, and granular in an aqueous emulsion to construct a coating with a sponge-like porous and capillary channel structure, and then uses siloxane to wrap and modify this porous and capillary channel structure. Then, on the basis of siloxane wrapping and modifying the porous and capillary channel stereostructure, a low-surface-energy polymer resin and nano-inorganic particles are further combined with this porous and capillary channel stereostructure, thereby enhancing the compactness, flame retardancy, and super-hydrophobicity of the coating. The whole process of coating preparation is carried out at room temperature, and no special treatment such as heating is required. The preparation method is simple and convenient. The coating integrates flame retardancy, corrosion resistance and super hydrophobicity, and has good application prospects in the fields of anti-seepage, anti-fouling, corrosion resistance and flame retardancy. Summary of the invention
[0003] The present invention solves the problems of single coating performance, weak adhesion, poor durability and complex manufacturing process, solves the problem of poor heat resistance efficiency of existing flame retardant materials, and solves the problem of low adhesion of inorganic nanoparticles in porous and capillary channel structures.
[0004] In order to solve the above problems, the present application is implemented through the following technical solutions: A method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material comprises the following steps: S1. Stirring a flame retardant filler, a water-based resin, a curing agent and water to obtain a base slurry; applying the base slurry evenly on a substrate and allowing it to stand to obtain a No. 1 coating; S2, stirring the siloxane and the first solvent after ultrasonic treatment to obtain a primary filler, and evenly coating the primary filler on the surface of the first coating prepared in step S1 to obtain a second coating; S3, mixing the second organic solvent, polymer resin and inorganic nanoparticles to obtain a secondary filler, evenly coating the secondary filler on the second coating prepared in step S2, and drying to obtain a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating.
[0005] In step S1, the bottom slurry comprises a flame retardant filler, a water-based resin, water and a curing agent, wherein, by weight, the flame retardant filler is 0.6 to 1.5 parts, the water-based resin is 3 to 7 parts, the water is 6 to 10 parts, and the curing agent is 2 to 5 parts; Wherein, the flame retardant filler is two or more of silicon dioxide, montmorillonite, soapstone powder, titanium dioxide, expanded graphite, fly ash, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, barium sulfate, zinc oxide, aluminum oxide, bentonite, sodium aluminum phosphate, zirconium oxide, carbon nanotubes, and magnesium silicate; The water-based resin includes one or more of water-based epoxy resin, polyvinyl alcohol, alkyd resin, fluorocarbon resin, water-based acrylic acid, and water-based polyurethane.
[0006] Among them, the curing agent is NX-8502.
[0007] In step S2, the siloxane is one or more of polydimethylsiloxane, methyltrimethoxysilane, vinyltriethoxysilane, phenyltrimethoxysilane, vinyltrimethoxysilane, vinylmethyldiethoxysilane, aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane, triethoxysilane and γ-mercaptopropyltriethoxysilane.
[0008] In step S2, the first solvent is one or more of anhydrous ethanol, ethyl acetate, isopropanol, acetone, ether or acetic acid, and tetrahydrofuran.
[0009] In the step S2, the volume ratio of the primary filler is siloxane: the first solvent = 5%-10%: 1.
[0010] In the step S3, the flame retardant, super hydrophobic, anti-seepage and anti-fouling multifunctional coating is calculated by weight: the base slurry: the primary filler: the secondary filler = 1.5~2.5:1:5~7.5.
[0011] In step S3, the secondary filler comprises a polymer resin, a second organic solvent and inorganic nanoparticles, wherein by weight, the polymer resin is 0.4-0.7 parts, the second organic solvent is 5-10 parts, and the inorganic nanoparticles are 0.4-0.7 parts.
[0012] The polymer resin in step S3 is one or more of polytetrafluoroethylene, polyvinylidene fluoride, fluorosilicone resin, fluorocarbon resin, silicone resin, dodecyl acrylate, polystyrene butadiene copolymer, and ethylene vinyl acetate.
[0013] In step S3, the second organic solvent is one or more of ethyl acetate, ethanol, n-hexane, isopropanol, diethyl ether, propanol, and dimethyl ether.
[0014] The inorganic nanoparticles in step S3 are one or more of nano silicon dioxide, nano aluminum hydroxide, nano aluminum oxide, nano magnesium hydroxide, nano titanium dioxide, nano sodium aluminum silicate or calcium aluminum phosphate.
[0015] Preferably, the flame retardant filler in step S1 is in the form of two or three of flake, fiber and granule.
[0016] Preferably, the particle size of the fibrous flame retardant filler in step S1 is 0.5-2.4 mm.
[0017] Preferably, the particle size of the flaky flame retardant filler in step S1 is 0.2-0.9 mm.
[0018] Preferably, in step S1, the particle size of the granular flame retardant filler is 0.5-1.0 mm.
[0019] Preferably, the standing time in step S1 is 40 to 60 minutes.
[0020] Preferably, in step S1, the method of coating the base slurry on the surface of the substrate is by scraping or spraying.
[0021] Preferably, in step S2, the ultrasonic time is 25 to 40 minutes, and the magnetic stirring time is 30 to 50 minutes.
[0022] Preferably, the particle size of the inorganic nanoparticles in step S3 is 20-200 nm.
[0023] Preferably, the drying time at room temperature in step S3 is 24 to 28 hours.
[0024] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention utilizes flame retardant fillers of different shapes, such as flake, fiber or granular, with obvious differences in shape and particle size to construct a coating with a sponge-like porous and capillary channel structure. This structure not only enhances the flame retardant properties of the material, but also facilitates the rapid penetration and low surface energy modification of subsequent siloxane solutions and inorganic nanoparticles.
[0025] 2. Use siloxane to wrap and modify the porous and capillary channel structure in the coating, on the one hand, to promote -CH n The groups and active Si-H bonds are covalently grafted to the surface of the porous and capillary channel structures with flame retardant fillers and water-based resins, thereby reducing the surface energy of the structure and enhancing the adhesion of subsequent inorganic nanoparticles in the porous and capillary channel structures.
[0026] 3. The porous and capillary channel structure inside the coating formed by wrapping and modifying the water-based resin is formed by siloxane penetration, so that the original hydrophilic water-based resin in the coating has hydrophobic properties after wrapping and modification.
[0027] 4. Mixing low surface energy polymer resin and inorganic nanoparticles and infiltrating them into the porous and capillary channel structure inside the coating after being wrapped and modified by siloxane, can not only make the inorganic nanoparticles fully fill the pores and capillary channels in the coating and improve the density of the material, but also enable them to firmly adhere to the surface of the porous and capillary channel structure inside the coating with the help of the siloxane wrapping modification in the previous process and the adhesion of the polymer resin itself, thereby optimizing the overall multi-level rough structure inside the coating; the penetration of inorganic nanoparticles into the holes in the filling structure also further hinders the penetration of water, further improving the overall self-similar structural characteristics, super hydrophobicity, anti-fouling and anti-seepage properties and flame retardant properties of the material.
[0028] 5. The material of the present invention is prepared at room temperature throughout the process, and does not require special high-temperature heating treatment, and can be widely used in practice. It is suitable for a variety of substrates, has strong adhesion properties, and a simple coating preparation method. This multifunctional coating material has strong adhesion, a simple preparation method, a wide range of applications, and excellent flame retardant, anti-seepage, anti-fouling and fire-resistant properties. It has good applications in anti-seepage, anti-fouling, corrosion resistance and flame retardancy in wood, plastic, and steel structure materials. DETAILED DESCRIPTION
[0029] The present invention uses wood and steel plate as coating substrates for the convenience of description or testing, but does not limit the application of the coating.
[0030] Soapstone powder was purchased from Guzhang County Shanlin Shiyu Mineral Products Co., Ltd., production model SA240118; expanded graphite was purchased from Guangzhou Metal Metallurgy Co., Ltd., production model C-10; fly ash was purchased from Henan Hengyuan New Materials Co., Ltd., the main components of which are silicon dioxide, calcium oxide and aluminum oxide; bentonite was purchased from Zhejiang Hongyu New Materials Co., Ltd., production model HY-708; montmorillonite was purchased from Lingshou County Dehang Mineral Products Co., Ltd., the main components of which are silicate, aluminum oxide and magnesium oxide; Water-based resin: Water-based epoxy resin was purchased from Shenyang Dongyan Paint Decoration Co., Ltd., manufacturer DY-175; polyvinyl alcohol was purchased from Aladdin, manufacturer P139535; alkyd resin was purchased from Shandong Aohui Paint Industry Group Co., Ltd., manufacturer 389-9A; water-based acrylic acid was purchased from Shenzhen Yoshida Chemical Co., Ltd., manufacturer E0504; water-based polyurethane was purchased from Shenzhen Yoshida Chemical Co., Ltd., manufacturer F0401; Siloxane: polydimethylsiloxane was purchased from Shanghai Deji Trading Co., Ltd., model H047N6N175; polytetrafluoroethylene was purchased from McLean, model 767293; polyvinylidene fluoride was purchased from Aladdin, model P432380; Fluorosilicone resin was purchased from Xinan Chemical New Materials Co., Ltd., production model FS-001; fluorocarbon resin was purchased from Shandong Huaxia Shenzhou New Materials Co., Ltd., production model DS301; Epoxy-modified silicone resin was purchased from Shenzhen Weiteli Environmental Protection Materials Co., Ltd. VR2404 production model; Behenyl acrylate was purchased from Aladdin, model D579667; polystyrene butadiene copolymer was purchased from Aladdin, model P394889; ethylene vinyl acetate was purchased from Aladdin, model P101482; The curing agent is water-based epoxy curing agent NX-8502, purchased from Cardolite Chemical Co., Ltd. If not otherwise specified, in the following examples or comparative examples, the heating temperature is set at 437°C, and the maximum back temperature of the blank steel plate without coating is 437°C. If not otherwise specified, the contact angle and rolling angle test objects of the coating are all water.
[0031] The saturated water absorption rate in the comparative example is 12%. The substrates in the embodiment and the comparative example are exactly the same, and the substrate mass is 6g. Definition: coating water absorption rate = (mass of substrate and coating after water absorption - mass of substrate and coating before water absorption) / substrate mass.
[0032] Example 1 Step 1, in terms of mass fractions, solid flame retardant filler configuration: weigh 0.1 parts of granular silica with a particle size of 0.5 mm, 0.1 parts of fibrous alumina with a particle size of 0.5 mm, and 0.4 parts of flaky expanded graphite with a particle size of 0.2 mm; place the solid flame retardant filler and 6 parts of water in a beaker and stir them thoroughly at a stirring speed of 300 r / min to obtain a uniform solution; weigh 3 parts of water-based epoxy resin and 2 parts of water-based epoxy curing agent NX-8502 and slowly add them to the solution in the previous step, mix them thoroughly and stir for 1 hour to obtain a uniform solution of the base slurry; apply it on the wood by brush, let it stand at room temperature for 1 hour, and obtain a No. 1 coating with a film thickness of 1 mm.
[0033] Step 2: Take 1 part of polydimethylsiloxane and 20 parts of the first solvent, anhydrous ethanol, in a beaker, perform ultrasonic treatment for 25 minutes, and then perform magnetic stirring for 30 minutes to uniformly disperse them to obtain a primary filler, which is uniformly sprayed on the surface of the No. 1 coating prepared in step 1 to obtain a No. 2 coating.
[0034] Step 3: Weigh 0.4 parts of polytetrafluoroethylene and 5 parts of the second organic solvent ethyl acetate in a beaker and stir them for 40 minutes until they are uniform, then weigh 0.2 parts of calcium aluminum phosphate with an average particle size of 20 nanometers and 0.2 parts of silicon dioxide with an average particle size of 40 nanometers into the solution and stir for 30 minutes to obtain a uniform solution of the secondary filler. Spray or scrape it on the surface of the No. 2 coating treated in step 2 for penetration, and dry it at room temperature for 24 hours.
[0035] In terms of mass percentage, base slurry: primary filler: secondary filler = 1.9:1:5.8.
[0036] Through the above steps, a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material is obtained after complete drying. The contact angle of water on the coating surface is 159±1°, and the rolling angle is 3±0.5°. The steel plate with the coating was tested with a temperature tester, and the maximum back temperature of the steel plate was 247°C. The wood block with the coating was immersed in a sodium hydroxide solution with a pH of 13 for 20 days, and the contact angle of the coating was 155±1°. After being immersed in clean water for 20 days, the water absorption rate of the coating was 1.8%.
[0037] Example 2 Step 1. Weigh 0.2 parts of granular zirconium oxide with a particle size of 0.4 mm, 0.2 parts of fibrous montmorillonite with a particle size of 0.6 mm, and 0.5 parts of flaky expanded graphite with a particle size of 0.2 mm, and place them in a beaker with 6 parts of water and stir them thoroughly at a stirring speed of 300 r / min to obtain a uniform solution; weigh 3 parts of water-based polyurethane and 2 parts of water-based epoxy curing agent NX-8502 and slowly add them to the solution in the previous step, mix them thoroughly and stir for 1 hour to obtain a uniform solution; apply it on the wood by brush, let it stand at room temperature for 1 hour, and obtain a No. 1 coating with a film thickness of 1 mm.
[0038] Step 2: Take 2 parts of vinylmethyldiethoxysilane and 18 parts of the first solvent ethyl acetate in a beaker, ultrasonicate for 25 minutes, and then magnetically stir for 30 minutes to evenly disperse them to obtain a primary filler, which is evenly sprayed on the surface of the coating prepared in step 1 to obtain a second coating.
[0039] Step 3: Weigh 0.3 parts of polyvinylidene fluoride and 5 parts of the second organic solvent isopropanol in a beaker and stir them for 40 minutes until they are uniform, then weigh 0.2 parts of aluminum oxide with an average particle size of 20 nanometers and 0.2 parts of magnesium hydroxide with an average particle size of 40 nanometers into the solution and stir for 30 minutes to obtain a uniform solution of the secondary filler. Spray or scrape the solution on the surface of the coating treated in step 2 for penetration, and dry it at room temperature for 24 hours.
[0040] In terms of mass percentage, the base slurry: primary filler: secondary filler = 2:1:5.7.
[0041] Through the above steps, a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material is obtained after complete drying. The contact angle of water on the coating surface is 155±1°, and the rolling angle is 6±0.5°. The steel plate with the coating was tested with a temperature tester, and the maximum back temperature of the steel plate was 267°C. The wood block with the coating was immersed in a sodium hydroxide solution with a pH of 13 for 20 days, and the contact angle of the coating was 152±1°. After being immersed in clean water for 20 days, the water absorption rate of the coating was 2.3%.
[0042] Example 3 Step 1. Weigh 0.1 parts of granular aluminum oxide with a particle size of 0.4 mm, 0.1 parts of fibrous zirconium oxide with a particle size of 0.8 mm, and 0.5 parts of flaky magnesium silicate with a particle size of 0.2 mm, by mass, and place them in a beaker with 6 parts of water and stir them thoroughly at a stirring speed of 300 r / min to obtain a uniform solution; weigh 3 parts of water-based acrylic acid and 2 parts of water-based epoxy curing agent NX-8502 and slowly add them to the solution in the previous step, mix them thoroughly and stir for 1 hour to obtain a uniform solution; apply it on a wood substrate by brush, let it stand at room temperature for 1 hour, and obtain a No. 1 coating with a film thickness of 1 mm.
[0043] Step 2: Take 1 part of methyltrimethoxysilane and 22 parts of the first solvent ether in a beaker, ultrasonicate for 25 minutes, and then magnetically stir for 30 minutes to evenly disperse them to obtain a primary filler, which is evenly sprayed on the surface of the No. 1 coating prepared in step 1 to obtain a No. 2 coating.
[0044] Step 3: Weigh 0.4 parts of fluorosilicone resin and 5 parts of the second organic solvent propanol in a beaker and stir them for 40 minutes until they are uniform. Then weigh 0.1 parts of aluminum hydroxide with an average particle size of 20 nanometers and 0.3 parts of silicon dioxide with an average particle size of 40 nanometers and stir them for 30 minutes to obtain a uniform solution of the secondary filler. Spray or scrape it on the surface of the No. 2 coating treated in step 2 for penetration, and dry it at room temperature for 24 hours.
[0045] In terms of mass percentage, base slurry: primary filler: secondary filler = 1.95:1:5.8.
[0046] Through the above steps, a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material is obtained after complete drying. The contact angle of water on the coating surface is 153±1°, and the rolling angle is 6±0.5°. The steel plate with the coating was tested with a temperature tester, and the maximum back temperature of the steel plate was 271°C. The wood block with the coating was immersed in a sodium hydroxide solution with a pH of 13 for 20 days, and the contact angle of the coating was 152±1°. After being immersed in clean water for 20 days, the water absorption rate of the coating was 1.9%.
[0047] Example 4 Step 1. Weigh 0.3 parts of granular aluminum oxide with a particle size of 0.4 mm, 0.1 parts of fibrous titanium dioxide with a particle size of 0.5 mm, and 0.3 parts of flaky expanded graphite with a particle size of 0.2 mm, by mass, and place them in a beaker with 6 parts of water and stir them thoroughly at a stirring speed of 300 r / min to obtain a uniform solution; weigh 3 parts of water-based polyurethane and 2 parts of water-based epoxy curing agent NX-8502 and slowly add them to the solution in the previous step, mix them thoroughly and stir for 1 hour to obtain a uniform solution; apply it on a wood substrate by brush, let it stand at room temperature for 1 hour, and obtain a No. 1 coating with a film thickness of 1 mm.
[0048] Step 2: Take 1 part of aminopropyl triethoxysilane and 19 parts of the first solvent anhydrous ethanol in a beaker, ultrasonicate for 25 minutes, and then magnetically stir for 30 minutes to evenly disperse them to obtain a primary filler, which is evenly sprayed on the surface of the No. 1 coating prepared in step 1 to penetrate and obtain the No. 2 coating.
[0049] Step 3: Weigh 0.4 parts of polytetrafluoroethylene and 5 parts of the second organic solvent ethyl acetate in a beaker and stir them for 40 minutes until they are uniform. Then weigh 0.2 parts of aluminum hydroxide with an average particle size of 30 nanometers and 0.2 parts of silicon dioxide with an average particle size of 50 nanometers and stir them for 30 minutes to obtain a uniform solution of the secondary filler. Spray or scrape it on the surface of the No. 2 coating treated in step 2, and dry it at room temperature for 24 hours.
[0050] In terms of mass percentage, base slurry: primary filler: secondary filler = 1.95:1:5.8.
[0051] Through the above steps, a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material is obtained after complete drying. The contact angle of water on the coating surface is 153±1°, and the rolling angle is 5±0.5°. The steel plate with the coating was tested with a temperature tester, and the maximum back temperature of the steel plate was 258°C. The wood block with the coating was immersed in a sodium hydroxide solution with a pH of 13 for 20 days, and the contact angle of the coating was 153±1°. After being immersed in clean water for 20 days, the water absorption rate of the coating was 2.5%.
[0052] Comparative Example 1 A method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating, the method and steps are basically the same as those in Example 1, except that: the solid flame-retardant filler is 0.1 part of spherical silicon dioxide with a particle size of 0.5 mm, 0.1 part of spherical aluminum oxide with a particle size of 0.5 mm, and 0.4 part of spherical expanded graphite with a particle size of 0.2 mm. Finally, a No. 1 coating with a film thickness of 1 mm is obtained.
[0053] The contact angle of the coating surface is 117±1°, and the rolling angle is 21±0.5°, which does not meet the super-hydrophobic requirements. The coated steel plate was tested with a temperature tester, and the maximum back temperature of the steel plate was 252°C. The coated wood block was immersed in a sodium hydroxide solution with a pH of 13 for 10 days, and the contact angle of the coating was 96±1°. After being immersed in clean water for 10 days, the water absorption rate of the coating reached saturation. It does not meet the requirements of flame retardancy, super-hydrophobicity and anti-seepage.
[0054] The flame retardant fillers have the same shape, and the arrangement and stacking of the particles are not conducive to the formation of a capillary porous structure, which affects the penetration and modification of the solution in the subsequent steps and reduces the superhydrophobic property of the coating.
[0055] Comparative Example 2 A method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating, the method and steps are basically the same as those in Example 1, except that: the solid flame-retardant filler is 0.1 part of spherical silica with a particle size of 20 nm, 0.1 part of fibrous alumina with a particle size of 20 nm, and 0.4 part of flaky expanded graphite with a particle size of 20 nm; and finally a No. 1 coating with a film thickness of 1 mm is obtained.
[0056] The contact angle of the coating surface is 117±1°, and the rolling angle is 21±0.5°, which does not meet the super-hydrophobic requirements. The steel plate with the coating was tested with a temperature tester, and the maximum back temperature of the steel plate was 252°C. The wood block with the coating was immersed in a sodium hydroxide solution with a pH of 13 for 10 days, and the contact angle of the coating was 96±1°. After being immersed in clean water for 10 days, the water absorption rate of the coating reached saturation. It does not meet the requirements of flame retardancy, super-hydrophobicity and anti-seepage.
[0057] The particle size of the flame retardant filler is at the nanometer level and cannot form a porous capillary structure, which in turn affects the infiltration modification of polydimethylsiloxane in step 2. Polytetrafluoroethylene, nano-silica and calcium aluminum phosphate cannot penetrate and fill into the coating, greatly reducing the hydrophobic self-cleaning performance of the coating.
[0058] Comparative Example 3 A method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating, the method and steps are basically the same as those in Example 1, except that: the solid flame-retardant filler is 0.1 parts of spherical silica with a particle size of 2 mm, 0.1 parts of fibrous alumina with a particle size of 2 mm, and 0.4 parts of flaky expanded graphite with a particle size of 2 mm; and finally a No. 1 coating with a film thickness of 1 mm is obtained.
[0059] The contact angle of the coating surface is 146±1°, and the rolling angle is 9±0.5°, which does not meet the super-hydrophobic requirements. The coated steel plate was tested with a temperature tester, and the maximum back temperature of the steel plate was 254°C. The wood block with the coating was immersed in a sodium hydroxide solution with a pH of 13 for 10 days, and the contact angle of the coating was 131±1°. After being immersed in clean water for 10 days, the water absorption rate of the coating reached saturation. It does not meet the requirements of flame retardancy, super-hydrophobicity and anti-seepage.
[0060] This shows that the porous structure formed by the regular arrangement of particles with consistent particle sizes will limit the inflow and penetration paths of the slurry prepared in steps 2 and 3, resulting in uneven distribution of the slurry and difficulty in adhesion, making the coating unable to achieve a superhydrophobic effect.
[0061] Comparative Example 4 A method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating, the method and steps are basically the same as those in Example 1, except that: in step 3, inorganic particles with a particle size of 200 um are taken; and finally a coating No. 1 with a film thickness of 1 mm is obtained.
[0062] The contact angle of the coating surface is 134±1°, and the rolling angle is 12±0.5°, which does not meet the super-hydrophobic requirements. The steel plate with the coating was tested with a temperature tester, and the maximum back temperature of the steel plate was 248°C. The wood block with the coating was immersed in a sodium hydroxide solution with a pH of 13 for 3 days, and it lost its hydrophobicity. After being immersed in clean water for 5 days, the water absorption rate of the coating reached saturation. It does not meet the requirements of flame retardancy, super-hydrophobicity and anti-seepage.
[0063] In step 3, the inorganic particles are too large to be effectively filled and infiltrated into the coating, and a multi-level rough structure cannot be formed, so that the coating fails to meet the super-hydrophobic requirements and has reduced anti-seepage performance.
[0064] Comparative Example 5 A method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating, the method and steps are basically the same as those in Example 1, except that: the polydimethylsiloxane in step 2 is not added, and on the basis of step 1, the solution prepared in step 3 is infiltrated and modified, and dried at room temperature; finally, a coating No. 1 with a film thickness of 1 mm is obtained.
[0065] The contact angle of the coating surface is 141±1°, and the rolling angle is 13±0.5°. The steel plate with the coating was tested with a temperature tester, and the maximum back temperature of the steel plate was 249°C. The wood block with the coating was immersed in a sodium hydroxide solution with a pH of 13 for 7 days, and the super hydrophobicity was lost. After being immersed in clean water for 10 days, the water absorption rate of the coating reached saturation. It does not meet the requirements of flame retardancy, super hydrophobicity and anti-seepage.
[0066] Without polydimethylsiloxane to graft and modify the hydrophilic functional groups in the water-based epoxy resin, flame-retardant filler silica, and alumina in the base layer, the surface energy of the coating cannot be effectively reduced, resulting in a decrease in hydrophobic properties.
[0067] Comparative Example 6 A method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating, the method and steps are basically the same as those in Example 2, except that: in step 1, the amount of water-based epoxy resin used is 15 parts; and finally a coating No. 1 with a film thickness of 1 mm is obtained.
[0068] The contact angle of the coating surface is 147±1°, and the rolling angle is 10±0.5°. The steel plate with the coating was tested with a temperature tester, and the maximum back temperature of the steel plate was 267°C. The wood block with the coating was soaked in a sodium hydroxide solution with a pH of 13 for 30 days and lost its hydrophobicity. After soaking in clean water for 28 days, the water absorption rate of the coating reached saturation. The requirements of flame retardant superhydrophobicity are not met. In Comparative Example 6, the water-based epoxy resin is greater than the specified amount, but the superhydrophobic performance is not achieved.
[0069] Waterborne epoxy resin itself contains hydrophilic groups. Excessive use of it will increase the proportion of hydrophilic components in the overall system, increase the surface tension of the coating, make it more hydrophilic, and reduce the hydrophobic properties of the coating.
[0070] Comparative Example 7 A method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating, the method and steps are basically the same as those in Example 1, except that calcium aluminum phosphate is not added in step 3, the contact angle of the coating surface is 151±1°, and the rolling angle is 8±0.5°, which does not meet the super-hydrophobic requirements. The steel plate with the coating was tested with a temperature tester, and the maximum back temperature of the steel plate was 372°C. The wood block with the coating was immersed in a sodium hydroxide solution with a pH of 13 for 2 days to lose its hydrophobicity. Soaked in clean water for 7 days, the water absorption rate reached saturation. The requirements of flame retardant, super-hydrophobic and anti-seepage are not met.
[0071] Calcium aluminum phosphate can promote the carbonization of the coating at high temperature. The carbon layer formed can isolate oxygen and heat. Without calcium phosphate, the temperature of the steel back increases by about 1.5 times. It has good acid and alkali resistance and is not easily corroded. Without calcium aluminum phosphate, the temperature of the coated steel back will increase.
[0072] The above are preferred embodiments and comparative examples of the present invention, but the present invention is not limited to the contents disclosed in the embodiments. Therefore, any effects or modifications completed without departing from the method disclosed in the present invention fall within the scope of protection of the present invention.
Claims
1. A method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material, characterized in that: The steps include: S1. Stirring a flame retardant filler, a water-based resin, a curing agent and water to obtain a base slurry; applying the base slurry evenly on a substrate and allowing it to stand to obtain a No. 1 coating; S2, stirring the siloxane and the first solvent after ultrasonic treatment to obtain a primary filler, and evenly coating the primary filler on the surface of the first coating prepared in step S1 to obtain a second coating; S3, mixing the second organic solvent, polymer resin and inorganic nanoparticles to obtain a secondary filler, evenly coating the secondary filler on the second coating prepared in step S2, and drying to obtain a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating.
2. The method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material according to claim 1, characterized in that: In step S1, the bottom slurry comprises a flame retardant filler, a water-based resin, water and a curing agent, wherein, by weight, the flame retardant filler is 0.6 to 1.5 parts, the water-based resin is 3 to 7 parts, the water is 6 to 10 parts, and the curing agent is 2 to 5 parts; Wherein, the flame retardant filler is two or more of silicon dioxide, montmorillonite, soapstone powder, titanium dioxide, expanded graphite, fly ash, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, barium sulfate, zinc oxide, aluminum oxide, bentonite, sodium aluminum phosphate, zirconium oxide, carbon nanotubes, and magnesium silicate; Wherein, the water-based resin includes one or more of water-based epoxy resin, polyvinyl alcohol, alkyd resin, fluorocarbon resin, water-based acrylic acid, and water-based polyurethane; Among them, the curing agent is NX-8502.
3. The method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material according to claim 1, characterized in that: In step S2, the siloxane is one or more of polydimethylsiloxane, methyltrimethoxysilane, vinyltriethoxysilane, phenyltrimethoxysilane, vinyltrimethoxysilane, vinylmethyldiethoxysilane, aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane, triethoxysilane and γ-mercaptopropyltriethoxysilane.
4. The method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material according to claim 1, characterized in that: In step S2, the first solvent is one or more of anhydrous ethanol, ethyl acetate, isopropanol, acetone, ether or acetic acid, and tetrahydrofuran.
5. The method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material according to claim 1, characterized in that: In the step S2, the volume ratio of the primary filler is siloxane: the first solvent = 5%-10%:
1.
6. The method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material according to claim 1, characterized in that: In the step S3, the flame retardant, super hydrophobic, anti-seepage and anti-fouling multifunctional coating is calculated by weight: the base slurry: the primary filler: the secondary filler = 1.5~2.5:1:5~7.
5.
7. The method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material according to claim 1, characterized in that: In step S3, the secondary filler comprises a polymer resin, a second organic solvent and inorganic nanoparticles, wherein by weight, the polymer resin is 0.4-0.7 parts, the second organic solvent is 5-10 parts, and the inorganic nanoparticles are 0.4-0.7 parts.
8. The method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material according to claim 1, characterized in that: The polymer resin in step S3 is one or more of polytetrafluoroethylene, polyvinylidene fluoride, fluorosilicone resin, fluorocarbon resin, silicone resin, dodecyl acrylate, polystyrene butadiene copolymer, and ethylene vinyl acetate.
9. The method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material according to claim 1, characterized in that: In step S3, the second organic solvent is one or more of ethyl acetate, ethanol, n-hexane, isopropanol, diethyl ether, propanol, and dimethyl ether.
10. The method for preparing a flame-retardant, super-hydrophobic, anti-seepage and anti-fouling multifunctional coating material according to claim 1, characterized in that: The inorganic nanoparticles in step S3 are one or more of nano silicon dioxide, nano aluminum hydroxide, nano aluminum oxide, nano magnesium hydroxide, nano titanium dioxide, nano sodium aluminum silicate or calcium aluminum phosphate.
Citation Information
Patent Citations
Water-based ultrathin fireproof coating for steel structure and preparation method thereof
CN111534181A
Wear-resistant and stable flame-retardant super-hydrophobic / super-oleophobic coating and preparation and application thereof
CN113105777A
Flame-retardant, super-wear-resistant and super-hydrophobic three-layer coating as well as preparation and application thereof
CN113292905A
Flame-retardant super-amphiphobic metal slow-release anticorrosive coating material and preparation method thereof
CN118027781A
Functional coatings comprising microspheres and nanofibers
US20220135838A1
Cited By
Preparation method of diffuse reflection coating
CN120169651A